The dialogic Education: Models, Approaches, and its Implementation - Elok Putri Nimasari; Slamet Setiawan; Ahmad Munir; Suhartono (ELITE JOURNAL, 2023)
ABSTRACT Dialogic education refers to the interaction occurred in a group work dialogue between teacher and students. It is not limited to written and verbal discourse; it also encompasses the broader notion that the interaction of diverse ideas can result in mutual insights. The concept of dialogic education involves how teachers elicit students' 'common sense' perspectives through classroom dialogue, interact with their emerging ideas, and assist students in overcoming misunderstandings during the learning process. By analyzing and creating dialogic interactions principals in the classroom, dialogic education not only stimulates broader and more comprehensive thinking and learning among students, but it also transforms classroom relationships, realigning the conventional power structure between teachers and students. This paper reviews the importance of the dialogic education by giving discussion on the models of the dialogic education, the approaches to study the dialogic education, and its implementation across countries. This paper also concludes the review by adding some future research direction according to the novelty and gaps from the earlier literature. Keywords: conversation analysis, corpus linguistics, dialogic education, sociocultural discourse analysis, thematic content analysis